Pengaruh Penambahan Asbuton LGA 50/30 pada Campuran AC-WC dengan Inovasi Limbah Styrofoam - Ramadhan, Luthfiano Ikhsan; Pristyawati, Tantin; Devi, Rida Handiana (Jurnal Talenta Sipil, 2024)
Indonesia’s road infrastructure requires 1.2 million tons of asphalt annually, but Pertamina can only supply 600,000 tons. This deficit compels the government and related stakeholders to seek alternatives to meet national asphalt needs and maintain road quality. This study aims to analyze the effects of adding Asbuton LGA 50/30 to Asphalt Concrete Wearing Course (AC-WC) with an innovative use of styrofoam waste. Experimental research was conducted to evaluate Marshall characteristics, including VMA (Void in Mineral Aggregate), VIM (Void in Mix), stability, VFA (Void Filled with Asphalt), and Marshall Quotient (MQ). Five styrofoam waste mix variations were tested at 2%, 4%, 6%, 8%, and 10% levels. For the 8% Asbuton mix, the highest stability was observed with 10% styrofoam, yielding a stability value of 2032.16 kg, VMA of 16.63%, VFA of 78.28%, VIM of 3.61%, flow of 2.45 mm, and MQ of 830.33 kg/mm. For the 9% Asbuton mix, the highest stability was achieved with 2% styrofoam, resulting in a stability value of 1882.35 kg, VMA of 16.21%, VFA of 80.17%, VIM of 3.24%, flow of 2.57 mm, and MQ of 735.72 kg/mm. The 10% and 2% styrofoam variations proved to be the most effective for AC-WC asphalt mixtures, as their Marshall values met the 2018 Bina Marga General Specifications, indicating that these styrofoam waste additions are optimal for AC-WC asphalt mixtures.